Diagnostic Values of Dermatoscopy and CD31 Expression in Cutaneous Lymphangioma Circumscriptum - Lu, Lixia; Yan, Siyu; Chen, Mingliang; Huang, Xiaoyan; Su, Juan (Frontiers in Medicine, 2021)
Background: Cutaneous lymphangioma circumscriptum is characterized by clusters of deep-seated, vesicle-like papules. Cutaneous lymphangioma circumscriptum (CLC) is not a tumor but rather a congenital malformation of superficial lymphatics. Objectives: The study aimed to describe the dermoscopic features of CLC and investigate the reason why marked blood components in CLC. Moreover, this study sought to increase awareness of the clinical characteristics of CLC and provide insights into CLC diagnosis. Methods: A representative sample of patients with CLC with demographic information and pathological and dermoscopical results was analyzed. The immunohistochemistry of lymphangioma specimens with CD31 and D2-40 was performed. The clinical manifestations of CLC, demographic information, and the results of immunohistochemistry were statistically analyzed to validate the correlation. Results: Besides the pattern of frog spawn-like blisters, lymphangioma also presented as either transparent or pigmented with dark-red to whitish/yellowish shades. Moreover, lymphangioma manifested as a pattern of dermatofibroma. Furthermore, CD31 was detected in the flattened endothelium and only present in dilated spaces containing enough blood or lymph components. Limitations: This study is limited by its retrospective nature and statistical power. Conclusion: Dermoscopy is useful for the diagnosis of CLC. CD31 positive staining and cystic-dilated spaces showed flattened inner and outer endothelia are the diagnostic features in hypopyon-like shape and blisters resembling frog spawn patterns in CLC. These features can assist in the diagnosis of CLC.